Mechanical, antibacterial, and biocompatibility mechanism of PVD grown silver–tantalum-oxide-based nanostructured thin film on stainless steel 316L for surgical applications - Alias, Rodianah; Mahmoodian, Reza; Genasan, Krishnamurithy; Vellasamy, Kumutha Malar; Abd Shukor, Mohd Hamdi; Kamarul, Tunku (Elsevier, 2020)
Surgical site infection associated with surgical instruments has always been a factor in delaying post-operative recovery of patients. The evolution in surface modification of surgical instruments can be a potential choice to overcome the nosocomial infection mainly caused by bacterial populations such as Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. A study was, therefore, conducted characterising the morphology, hydrophobicity, adhesion strength, phase, Nano-hardness, surface chemistry, antimicrobial and biocompatibility of SS 316L steel deposited with a Nano-composite layer of Silver (Ag) and Tantalum oxide (Ta2O5) using physical vapour deposition magnetron sputtering. The adhesion strength of Ag/AgTa2O5 coating on SS 316L and treated at 250–850 °C of thermal treatment was evaluated using micro-scratch. The Ag/Ag–Ta2O5-400 °C was shown a 154% improvement in adhesion strength on SS 316L when compared with as-sputtered layer or Ag/Ag–Ta2O5-250, 550, 700 and 850 °C. The FESEM, XPS, and XRD indicated the segregation of Ag on the surface of SS 316L after the crystallization. Wettability and Nano-indentation tests demonstrated an increase in hydrophobicity (77.3 ± 0.3°) and Nano-hardness (1.12 ± 0.43 GPa) when compared with as-sputtered layer, after the 400 °C of thermal treatment. The antibacterial performance on Ag/Ag–Ta2O5-400 °C indicated a significant zone of inhibition to Staphylococcus aureus (A-axis: 16.33 ± 0.58 mm; B-axis: 25.67 ± 0.58 mm, p < 0.01) and Escherichia coli (A-axis: 16.33 ± 1.15 mm; B-axis: 26.00 ± 0.00 mm, p < 0.01) when compared with SS 316L or Ag/Ag–Ta2O5-700 °C, which showed no inhibition. The biocompatibility tests on Ag/Ag–Ta2O5-400 °C demonstrated an excellent in cell attachment, F-actin protein expression and proliferation/viability of bone marrow derived mesenchymal stromal on day 14 when compared with uncoated or Ag/Ag–Ta2O5-700 °C. This study shows that the Ag segregation process, hydrophobicity, adhesion strength, crystallization, and hardness progressively improved after the annealing up to 400 °C. © 2019 Elsevier B.V.